Person-centered osteopathic practice: patients’ personality (body, mind, and soul) and health (ill-being and well-being) - Elin Fahlgren; Ali A. Nima; Trevor Archer; Danilo Garcia (PeerJ, 2015)
Background. Osteopathic philosophy and practice are congruent with the biopsychosocial model, a patient-centered approach when treating disease, and the view of the person as a unity (i.e., body, mind, and soul). Nevertheless, a unity of being should involve a systematic person-centered understanding of the patient’s personality as a biopsychosociospiritual construct that influences health (i.e., well-being and ill-being). We suggest Cloninger’s personality model, comprising temperament (i.e., body) and character (i.e., mind and soul), as a genuine paradigm for implementation in osteopathic practice. As a first step, we investigated (1) the relationships between personality and health among osteopathic patients, (2) differences in personality between patients and a control group, and (3) differences in health within patients depending on the presenting problem and gender.Method. 524 osteopathic patients in Sweden (age mean = 46.17, SD = 12.54, 388 females and 136 males) responded to an online survey comprising the Temperament and Character Inventory and measures of health (well-being: life satisfaction, positive affect, harmony in life, energy, and resilience; ill-being: negative affect, anxiety, depression, stress, and dysfunction and suffering associated to the presenting problem). We conducted two structural equation models to investigate the association personality-health; graphically compared the patients’ personality T-scores to those of the control group and compared the mean raw scores using t-tests; and conducted two multivariate analyses of variance, using age as covariate, to compare patients’ health in relation to their presenting problem and gender.Results. The patients’ personality explained the variance of all of the well-being (R2 between .19 and .54) and four of the ill-being (R2 between .05 and .43) measures. Importantly, self-transcendence, the spiritual aspect of personality, was associated to high levels of positive emotions and resilience. Osteopathic patients, compared to controls, scored higher in six of the seven personality dimensions. These differences were, however, not considerably large (divergences in T-scores were <1 SD, Cohen’s d between 0.12 and 0.40). Presenting problem and gender did not have an effect on any of the health measures.Conclusion. The patient’s personality as a ternary construct (i.e., body, mind, and soul), which is in line with osteopathy, is associated to both well-being and ill-being. The lack of substantial differences in personality between patients and controls implies that the patients had not any personality disorders. Hence, osteopaths might, with proper education, be able to coach their patients to self-awareness. The lack of differences in health variables between osteopathic patients with different presenting problems suggests that practitioners should focus on the person’s health regardless of the type of presenting problem.